2021
DOI: 10.3390/cancers13040794
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Low-Grade, Early-Stage Endometrial Carcinoma Reveals New Dysregulated Pathways Associated with Cell Death and Cell Signaling

Abstract: Low-grade, early-stage endometrial carcinoma (EC) is the most frequent malignant tumor of the uterine corpus. However, the molecular alterations that underlie these tumors are far from being fully understood. The purpose of this study is to describe dysregulated molecular pathways from EC patients. Sixteen samples of tumor tissue and paired healthy controls were collected and both were subjected to mass spectrometry (MS)/MS proteomic analysis. Gene ontology and pathway analysis was performed to discover dysreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…Ferroptosis releases damage-related molecular patterns that can be sensed by immune cells to amplify the inflammatory response. With the advent of immunotherapy, people are increasingly aware of the impact of the immune microenvironment on cancer behavior and clinical outcomes ( López-Janeiro et al, 2021 ). Furthermore, we found that activated CD8 T cells, eosinophils, CD56dim natural killer cells, and activated B cells are good prognostic factors for EC, which is basically consistent with the research results of the previous research ( López-Janeiro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis releases damage-related molecular patterns that can be sensed by immune cells to amplify the inflammatory response. With the advent of immunotherapy, people are increasingly aware of the impact of the immune microenvironment on cancer behavior and clinical outcomes ( López-Janeiro et al, 2021 ). Furthermore, we found that activated CD8 T cells, eosinophils, CD56dim natural killer cells, and activated B cells are good prognostic factors for EC, which is basically consistent with the research results of the previous research ( López-Janeiro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of immunotherapy, people are increasingly aware of the impact of the immune microenvironment on cancer behavior and clinical outcomes ( López-Janeiro et al, 2021 ). Furthermore, we found that activated CD8 T cells, eosinophils, CD56dim natural killer cells, and activated B cells are good prognostic factors for EC, which is basically consistent with the research results of the previous research ( López-Janeiro et al, 2021 ). Activated CD8 T cells and eosinophils have been widely verified to have significant antitumor effects ( Sakkal et al, 2016 ; Loo Yau et al, 2021 ; Pauken et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid differences in the amount of protein labeled by each TMT reagent, the total sum of signals of each channel were corrected by computing normalization factors to equal these sums. Sample loading (SL) normalization was carried out with R Studio (version 4.1.1) according to established protocol (https://github.com/pwilmart, accessed on 15 May 2020), using "tidyverse", "psych", "gridExtra" and "scales" packages (Figure S1) [26,27]. Data were then exported to Microsoft Excel 2019 and Perseus (Version 1.6.6) for the subsequent analysis.…”
Section: Ms Data Analysismentioning
confidence: 99%
“…In addition, other genes such as retinoblastoma (Rb), nuclear factor erythroid 2-related factor 2 (NRF2), and metallothionein (MT)-1G are reported to be associated with ferroptosis and protect liver cancer from induction of sorafenib (Louandre et al, 2015;Sun et al, 2016a,b). In 2021, researchers have revealed that ferroptosis process was aberrantly regulated in UCEC and an activator of ferroptosis can induce cell death in UCEC cells (Lopez-Janeiro et al, 2021;Zhang et al, 2021). However, the prognosis value of ferroptosis in the endometrial carcinoma still remains blank.…”
Section: Introductionmentioning
confidence: 99%